Coated positive electrode material, preparation method thereof, positive electrode sheet, and lithium ion battery

CN122930877APending Publication Date: 2026-10-16SHANGHAI XUANYI NEW ENERGY DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611198276.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-07
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0005]本发明的主要目的在于提供一种包覆型正极材料、其制备方法、正极极片以及锂离子电池,以解决现有技术中的包覆型正极材料的电化学活性与循环稳定性欠佳的问题

Benefits of technology

[0023] Firstly, the synergistic conductivity mechanism: the high conductivity and tight coating structure of two-dimensional non-metallic materials ensure rapid charge transport during battery cycling, significantly improving the material's electronic conductivity. Meanwhile, transition metal sulfides and selenides, due to their unique layered structure, provide rapid ion diffusion pathways, increasing the diffusion rate of lithium ions during charging and discharging. At the heterojunction interface, the lattice matching and electronic coupling of the two materials generate additional ion transport channels, further enhancing the conductivity of Li. + The diffusion coefficient is increased, thereby reducing the interface resistance of the battery and improving its rate performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122930877A_ABST
    Figure CN122930877A_ABST
Patent Text Reader

Abstract

The application provides a coated positive electrode material, a preparation method thereof, a positive electrode sheet and a lithium ion battery. The coated positive electrode material comprises core particles and an outer coating layer, the core particles are selected from one or more of phosphate materials, nickel-cobalt-manganese ternary materials and lithium-rich manganese-based materials; the outer coating layer comprises a first coating layer and a second coating layer in the direction away from the core particles; the first coating layer comprises a two-dimensional non-metallic material, the second coating layer comprises a transition metal sulfide and / or a transition metal selenide, and a heterojunction interface layer is formed between the first coating layer and the second coating layer through van der Waals force. The application adopts a multi-layer coating mode, constructs a synergistic coating structure composed of a two-dimensional non-metallic layer and a transition metal compound layer on the surface of the positive electrode active material, and then forms a heterojunction interface layer, so that the electronic conductivity, ion transmission rate and structural stability of the lithium ion battery positive electrode material are simultaneously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion batteries, and more specifically, to a coated cathode material, its preparation method, a cathode sheet, and a lithium-ion battery. Background Technology

[0002] Since their commercialization in the 1990s, lithium-ion batteries (LIBs) have become the primary power source for modern mobile electronic devices and have demonstrated enormous potential in electric vehicles and large-scale energy storage systems. However, as energy storage devices evolve to demand higher energy density, longer cycle life, and faster charge / discharge rates, currently commercially available lithium-ion battery cathode materials, such as lithium cobalt oxide (LiCoO2), lithium nickel cobalt manganese oxide (LiNixCoyMnzO2), and lithium iron phosphate (LiFePO4), are gradually revealing their limitations. Especially in the electric vehicle sector, higher energy density translates to longer driving range, a requirement that current cathode materials struggle to meet, while also facing challenges related to cost, resource sustainability, and safety.

[0003] To improve the performance of cathode materials, researchers have adopted various strategies, the most common being surface modification techniques, including but not limited to surface coating, doping, and surface coating itself. Surface coating involves covering the surface of cathode material particles with a thin layer of conductive or insulating material to improve the material's electronic and ionic conductivity while protecting it from electrolyte corrosion. Currently, commonly used coating materials include carbon materials, metal oxides, and conductive polymers. However, each material has its unavoidable limitations, and a comprehensive coating solution that can fully address these issues is lacking.

[0004] Therefore, how to provide a new coated cathode material to significantly improve its electrochemical activity and cycle stability is one of the technical problems that need to be solved in this field. Summary of the Invention

[0005] The main objective of this invention is to provide a coated cathode material, its preparation method, cathode sheet, and lithium-ion battery to solve the problems of poor electrochemical activity and cycle stability of coated cathode materials in the prior art.

[0006] To achieve the above objectives, a first aspect of the present invention provides a coated cathode material, comprising core particles and an outer coating layer, wherein the core particles are selected from one or more of phosphate materials, nickel-cobalt-manganese ternary materials, and lithium-rich manganese-based materials; the outer coating layer comprises a first coating layer and a second coating layer along the direction away from the core particles; the first coating layer comprises a two-dimensional non-metallic material, the second coating layer comprises a transition metal sulfide and / or a transition metal selenide, and a heterojunction interface layer is formed between the first coating layer and the second coating layer by van der Waals forces.

[0007] Furthermore, the particle size of the core particles is 2μm~5μm; the thickness of the outer coating layer is 2nm~20nm, and the thickness ratio of the first coating layer to the second coating layer is 1:(1~3); preferably, the thickness of the first coating layer is 1nm~5nm; and / or, the thickness of the second coating layer is 1nm~15nm.

[0008] Furthermore, the first coating layer includes one or more of graphene, reduced graphene, and boron nitride nanosheets; and / or, in the second coating layer, the transition metal sulfide is selected from one or more of MoS2, WS2, VS2, and NbS2, and the transition metal selenide is MoSe2 and / or WSe2.

[0009] A second aspect of the present invention provides a method for preparing a coated cathode material, comprising: step S1, performing surface hydroxylation treatment on cathode material particles to obtain a first product; step S2, performing an electrostatic adsorption reaction between the first product and a two-dimensional non-metallic material to form a first coating layer on the surface of the first product, thereby obtaining a second product; step S3, performing a hydrothermal reaction between the second product and a coating solution to obtain a third product; the coating solution includes a transition metal source, and further includes a sulfur source and / or a selenium source; during the hydrothermal reaction, the transition metal source reacts in situ with the sulfur source and / or the selenium source and coats the surface of the second product to form a second coating layer, thereby obtaining the third product; step S4, subjecting the third product to heat treatment to obtain a coated cathode material.

[0010] Further, step S1 includes: dispersing the cathode material particles in a hydroxylation solvent containing alcohols, and performing surface hydroxylation treatment by ultrasound to obtain a first product; the solid-liquid ratio of the cathode material particles to the hydroxylation solvent is 1 g: (50 mL~150 mL); the frequency of the ultrasound treatment is 30 kHz~60 kHz, and the time is 20 min~40 min; the alcohols are selected from one or more of ethanol, ethylene glycol and isopropanol.

[0011] Further, step S2 includes: preparing a dispersion of a two-dimensional non-metallic material, adding the first product to the dispersion, and performing an electrostatic adsorption reaction by stirring to form a first coating layer on the surface of the first product, thereby obtaining the second product; the concentration of the two-dimensional non-metallic material in the dispersion is 1±0.05 mg / mL; the solid-liquid ratio of the first product to the dispersion is 1 g:(80 mL~200 mL); the two-dimensional non-metallic material is graphene and / or boron nitride nanosheets; the stirring speed is 300 rpm~800 rpm, and the stirring time is 1.5 h~2.5 h; preferably, the two-dimensional non-metallic material is graphene, and step S2 further includes: using ascorbic acid to reduce the second product to reduce the graphene in the first coating layer to reduced graphene; more preferably, the reaction temperature of the reduction treatment is 80±5℃, and the time is 1.5 h~2.5 h; more preferably, the weight ratio of the second product to ascorbic acid is (10~20):1.

[0012] Further, in step S3, the concentration of the transition metal source in the coating solution is 0.04M~0.06M, and the concentrations of the sulfur source and selenium source are each independently 0~0.1M; the solid-liquid ratio of the second product to the coating solution is 1g:(100mL~300mL); the hydrothermal reaction temperature is 200±20℃, and the time is 12±2h; preferably, the transition metal source is selected from one or more of molybdenum source, tungsten source, vanadium source, and niobium source; the sulfur source is selected from one or more of thiourea, thioacetamide, and sodium sulfide; the selenium source is selected from one or more of selenourea, selenium dioxide, and sodium selenite; more preferably, the molybdenum source is selected from one or more of ammonium molybdate, sodium molybdate, and calcium molybdate; the tungsten source is selected from one or more of ammonium tungstate, tungsten hexachloride, and sodium tungstate; the vanadium source is selected from one or more of ammonium metavanadate, vanadium pentoxide, and vanadium trichloride; and the niobium source is selected from one or more of niobium pentachloride, niobium oxalate, and ammonium niobate.

[0013] Further, in step S4, the heat treatment temperature is 300℃~500℃ and the time is 1h~3h; the heat treatment is carried out in a protective atmosphere or a reducing atmosphere, and the protective atmosphere is nitrogen and / or argon, and the reducing atmosphere is a mixture of hydrogen and argon, wherein the hydrogen gas fraction is 5%~10%.

[0014] A third aspect of the present invention provides a positive electrode sheet comprising the above-described coated positive electrode material; or, the positive electrode sheet comprising a coated positive electrode material prepared by the above-described method for preparing the coated positive electrode material.

[0015] A fourth aspect of the present invention provides a lithium-ion battery comprising the aforementioned positive electrode.

[0016] By employing the technical solution of this invention, a multi-layer coating method is used to construct a synergistic coating structure consisting of a two-dimensional non-metallic layer and a transition metal compound layer on the surface of the positive electrode active material, thereby forming a heterojunction interface layer. This achieves the goal of simultaneously improving the electronic conductivity, ion transport rate, and structural stability of the lithium-ion battery positive electrode material, thereby significantly enhancing the battery cycle performance, voltage retention rate, and rate characteristics, as well as effectively suppressing the dissolution of transition metals and the decomposition of electrolyte. Attached Figure Description

[0017] The accompanying drawings, which form part of this application, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. In the drawings:

[0018] Figure 1 The transmission electron microscope (TEM) characterization results of the coated cathode material obtained in Example 1 of this invention are shown. Detailed Implementation

[0019] It should be noted that, unless otherwise specified, the embodiments and features described in this application can be combined with each other. The present invention will now be described in detail with reference to the embodiments.

[0020] As described in the background section, existing coated cathode materials suffer from poor electrochemical activity and cycle stability due to poor electronic conductivity, ion transport rate, and structural stability. To address these technical problems, a first aspect of the present invention provides a coated cathode material comprising core particles and an outer coating layer. The core particles are selected from one or more of phosphate-based materials, nickel-cobalt-manganese ternary materials, and lithium-rich manganese-based materials. Along the direction away from the core particles, the outer coating layer comprises a first coating layer and a second coating layer. The first coating layer comprises a two-dimensional non-metallic material, and the second coating layer comprises a transition metal sulfide and / or a transition metal selenide. A heterojunction interface layer is formed between the first and second coating layers through van der Waals forces.

[0021] This invention constructs a synergistic coating structure consisting of a two-dimensional non-metallic layer and a transition metal compound layer on the surface of the positive electrode active material, thereby forming a heterojunction interface layer and obtaining a high-performance coated positive electrode material. Specifically, the electronic conductivity of the two-dimensional non-metallic material layer significantly reduces the resistance to charge transport, while the transition metal chalcogenides and / or transition metal selenides provide rapid Li-ionization. +The diffusion pathway and the synergistic effect of both significantly improve the electrochemical activity and kinetic response of the material. Furthermore, the heterojunction structure formed between the two coating layers by van der Waals forces effectively buffers the volume changes of the cathode material during charge and discharge, suppresses irreversible structural phase transitions, and enhances the structural stability and cycle life of the material. Regarding interface protection, this special coating design forms a more stable CEI layer, reduces side reactions between the cathode material and the electrolyte, lowers interfacial impedance, and ensures good battery performance at high voltages.

[0022] More specifically, the coating material provided by this invention has the following advantages:

[0023] Firstly, the synergistic conductivity mechanism: the high conductivity and tight coating structure of two-dimensional non-metallic materials ensure rapid charge transport during battery cycling, significantly improving the material's electronic conductivity. Meanwhile, transition metal sulfides and selenides, due to their unique layered structure, provide rapid ion diffusion pathways, increasing the diffusion rate of lithium ions during charging and discharging. At the heterojunction interface, the lattice matching and electronic coupling of the two materials generate additional ion transport channels, further enhancing the conductivity of Li. + The diffusion coefficient is increased, thereby reducing the interface resistance of the battery and improving its rate performance.

[0024] Secondly, the structural stability effect: The presence of the first and second coating layers, especially the heterojunction interface layer between them, significantly impacts the structural stability of the cathode material. The flexibility of the two-dimensional non-metallic material can adapt to the volume changes of the cathode material during charging and discharging, providing strain buffering and preventing particle breakage. Simultaneously, the layered structure of transition metal sulfides / selenides at the heterojunction interface, through an electronic coupling mechanism, suppresses the irreversible phase transition of the layered structure, thereby maintaining the structural integrity of the cathode material at the microscale and improving cycle stability.

[0025] Thirdly, the interface protection function: the heterojunction interface layer formed by the first and second coating layers at the electronic structure level not only promotes the coordinated transport of electrons and ions, but also acts as a physical and chemical barrier, protecting the cathode material from electrolyte corrosion. The low permeability of the two-dimensional non-metallic material prevents direct contact between electrolyte molecules, reducing the dissolution of transition metals. Furthermore, the polar surface of the transition metal sulfide / selenide layer interacts with the Li in the electrolyte. + The formation of weak coordination helps stabilize the CEI layer, reduces the occurrence of interfacial side reactions, and minimizes electrolyte decomposition, thereby maintaining the stability and efficiency of the battery at high voltage.

[0026] In summary, the specially structured coated cathode material provided by this invention achieves the goal of simultaneously improving the electronic conductivity, ion transport rate, and structural stability of lithium-ion battery cathode materials, thereby significantly enhancing battery cycle performance, voltage retention rate, and rate capability, as well as effectively suppressing transition metal dissolution and electrolyte decomposition.

[0027] Specifically, phosphate materials can be lithium iron phosphate (LiFePO4) and lithium manganese iron phosphate (LiMn). x Fe 1-x PO4 (0.1≤x≤0.9), lithium manganese phosphate (LiMnPO4), nickel-cobalt-manganese ternary materials specifically include NCM523, NCM622, and NCM811, and lithium-rich manganese-based materials specifically include Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2, Li 1.2 Ni 0.2 Mn 0.6 O2, Li 1.2 Ni 0.15 Co 0.1 Mn 0.55 O2.

[0028] In several preferred embodiments, the microstructure parameters of the above-mentioned coated cathode material are preferably as follows: the particle size of the core particles is 2 μm to 5 μm; the thickness of the outer coating layer is 2 nm to 20 nm, and the thickness ratio of the first coating layer to the second coating layer is 1:(1 to 3). The preferred core particle size helps to further shorten the diffusion path of lithium ions within the material, increasing the rate of the electrochemical reaction. The preferred range of the total thickness and thickness ratio of the two coating layers can more effectively protect the core particles and reduce the charge transport resistance increased by an excessively thick coating layer, thereby significantly improving the cycle stability and rate performance of the resulting coated cathode material while maintaining high energy density. Based on the above, in order to more effectively balance the needs of electron / ion conduction and structural protection, and thus more efficiently improve the overall performance of the coated cathode material, the thickness of the first coating layer is more preferably 1 nm to 5 nm; and / or, the thickness of the second coating layer is 1 nm to 15 nm (more preferably 2 nm to 6 nm).

[0029] Furthermore, the first coating layer includes one or more of graphene, reduced graphene, and boron nitride nanosheets; and / or, in the second coating layer, the transition metal sulfide is selected from one or more of MoS2, WS2, VS2, and NbS2, and the transition metal selenide is MoSe2 and / or WSe2. In particular, the high conductivity of graphene and reduced graphene in the first coating layer provides more electron channels for lithium-ion transport, while the ion conductivity of the aforementioned specific transition metal sulfides / selenides can enhance the lithium-ion transport capabilities. + The diffusion process provides a better environment. More importantly, the material selection of the first and second coating layers allows for better synergy at the electronic structure level, forming a better heterojunction interface layer. This significantly optimizes charge transport and separation, resulting in a significant improvement in the battery's rate performance and cycle stability while maintaining high energy density. Through extensive experimentation, the inventors further optimized the core particles to be phosphate-based materials or nickel-cobalt-manganese ternary materials, with the first coating layer being a reduced graphene layer and the second coating layer being a MoS2 layer. The electronic conductivity of the reduced graphene layer (rGO layer) combined with the ionic conductivity of the MoS2 layer, along with the electronic coupling effect of the heterojunction interface layer, further enhances the performance of the coated cathode material. In fact, when the rGO layer and the MoS2 layer come into contact, due to the difference in their work functions, electrons will transfer from the rGO layer to the MoS2 layer to achieve Fermi level equilibrium. At this point, the rGO layer becomes hole-doped, while the MoS2 layer becomes electron-doped, resulting in a significant increase in conductivity. This leads to the formation of a built-in electric field at the interface, i.e., the heterojunction interface layer, which provides a more multidimensional and stable conductive network for the charge. Furthermore, the aforementioned rGO + MoS2 layer coating combination significantly enhances the performance of high-energy-density cathode materials such as phosphate-based materials, nickel-cobalt-manganese ternary materials, and lithium-rich manganese-based materials, significantly reducing interfacial side reactions and improving structural stability and electrochemical cycling performance.

[0030] A second aspect of the present invention provides a method for preparing a coated cathode material, comprising: step S1, performing surface hydroxylation treatment on cathode material particles to obtain a first product; step S2, performing an electrostatic adsorption reaction between the first product and a two-dimensional non-metallic material to form a first coating layer on the surface of the first product, thereby obtaining a second product; step S3, performing a hydrothermal reaction between the second product and a coating solution to obtain a third product; the coating solution includes a transition metal source, and further includes a sulfur source and / or a selenium source; during the hydrothermal reaction, the transition metal source reacts in situ with the sulfur source and / or the selenium source and coats the surface of the second product to form a second coating layer, thereby obtaining the third product; step S4, subjecting the third product to heat treatment to obtain a coated cathode material.

[0031] To address the aforementioned coated cathode material, this invention provides a corresponding preparation method. Specifically: First, by hydroxylating the surface of the cathode material particles, the surface active functional groups are increased, creating favorable conditions for the subsequent electrostatic adsorption of two-dimensional non-metallic materials and promoting a tight bond between the coating layer and the core particles. Then, the two-dimensional non-metallic material adheres tightly to the surface of the cathode particles through electrostatic forces, forming a stable first coating layer. In step S3, during the hydrothermal reaction between the second product (i.e., the cathode material with the first coating layer) and the coating solution, a transition metal source reacts chemically with a sulfur source and / or a selenium source under high temperature and high pressure, resulting in the in-situ growth of a second coating layer (i.e., a transition metal sulfide or selenide). During this process, the newly coated second coating layer and the first coating layer work synergistically to form a heterojunction interface layer at the electronic structure level, thereby significantly improving the lithium-ion diffusion rate and enhancing the structural stability of the material. In particular, this in-situ growth method ensures strong interfacial bonding between the second coating layer and the core particles, as well as the first coating layer, reducing coating layer peeling during charging and discharging, thereby improving the structural stability of the final coated cathode material. Finally, heat treatment of the third product further enhances the bonding force between the coating layer and the core, optimizing the material's microstructure. Simultaneously, this heat treatment step also helps remove impurities and purify the surface of the resulting product, ultimately yielding a coated cathode material with high electronic conductivity, high ion transport rate, and high structural stability.

[0032] More specifically, the preferred step S1 includes: dispersing the cathode material particles in a hydroxylation solvent containing alcohols, and performing surface hydroxylation treatment by ultrasound to obtain a first product; the solid-liquid ratio of the cathode material particles to the hydroxylation solvent is 1 g:(50 mL~150 mL); the frequency of the ultrasound treatment is 30 kHz~60 kHz, and the time is 20 min~40 min. The preferred solid-liquid ratio promotes sufficient hydroxylation of the cathode particle surface while reducing its accumulation, further improving hydroxylation efficiency and uniformity, providing a better foundation for subsequent electrostatic adsorption coating. The optimized ultrasound conditions more effectively break the weak chemical bonds on the cathode material surface, exposing more active sites, increasing the number of surface hydroxyl groups, and thus significantly enhancing the adhesion of subsequent electrostatic adsorption and the coating layer.

[0033] In practical applications, the alcohols used for surface hydroxylation are selected from one or more of ethanol, ethylene glycol, and isopropanol. In several typical embodiments, a mixed solvent of ethanol and water is preferred, with a volume ratio of ethanol to water of (3-7):1. In this preferred mixed solvent system, ethanol, as a polar organic solvent, provides a more suitable medium environment for the hydroxylation reaction, while the presence of water promotes more uniform hydroxylation. Using the two in the aforementioned volume ratio further enhances the electrostatic interaction between the cathode material particles and the two-dimensional non-metallic material, promoting the formation of a denser and more uniform first coating layer. Furthermore, the cathode material particles can be selected from one or more of phosphate materials, nickel-cobalt-manganese ternary materials, and lithium-rich manganese-based materials.

[0034] In the process of forming the first coating layer, preferred step S2 includes: preparing a dispersion of a two-dimensional non-metallic material, adding the first product to the dispersion, and performing an electrostatic adsorption reaction by stirring, so that the two-dimensional non-metallic material forms a first coating layer on the surface of the first product, thereby obtaining a second product; the concentration of the two-dimensional non-metallic material in the dispersion is 1 ± 0.05 mg / mL; the solid-liquid ratio of the first product to the dispersion is 1 g: (80 mL ~ 200 mL). In the above preferred embodiment, the concentration range of 1 ± 0.05 mg / mL promotes more uniform dispersion of the two-dimensional non-metallic material in the dispersion, while providing sufficient coating source for coating, thereby improving the uniformity and thickness controllability of the first coating layer, and ultimately resulting in a coated cathode material with better ion transport channels. Furthermore, performing the electrostatic adsorption reaction within the above preferred solid-liquid ratio range can form a dense first coating layer and more effectively reduce the phenomenon of incomplete adsorption due to insufficient solution or excessive coating layer due to excessive solution, thereby significantly optimizing the electrochemical performance of the obtained coated cathode material at the microstructure level. Specifically, the two-dimensional non-metallic material is graphene and / or boron nitride nanosheets.

[0035] Furthermore, during the electrostatic adsorption process, the preferred stirring speed is 300 rpm to 800 rpm, and the time is 1.5 h to 2.5 h, so as to promote more uniform mixing of the first product and the dispersion, enhance the contact between them, accelerate the electrostatic adsorption process, and enable the first coating layer to be more uniformly distributed on the surface of the cathode material particles, thereby significantly improving the uniformity, consistency and structural stability of the obtained coated cathode material.

[0036] In several typical embodiments, to provide higher conductivity and form a more stable heterojunction interface layer with the subsequent second coating layer, further enhancing the electrochemical activity of the resulting coated cathode material, graphene is preferably used as the two-dimensional non-metallic material. Step S2 further includes: reducing the second product with ascorbic acid to reduce the graphene in the first coating layer to reduced graphene. Furthermore, in the reduction process, to more effectively reduce the oxide groups on the graphene surface and form a more stable carbon network structure, thereby further improving the electronic conductivity of the resulting coated cathode material, the reduction reaction temperature is preferably 80±5℃, and the time is 1.5h~2.5h. To minimize side reactions caused by excess ascorbic acid and more efficiently improve the electronic conductivity, ion transport efficiency, and structural stability of the resulting coated cathode material, the weight ratio of the second product to ascorbic acid is more preferably (10~20):1.

[0037] In step S3, the preferred concentration of the transition metal source in the coating solution is 0.04M~0.06M, and the concentrations of the sulfur source and selenium source are each independently 0~0.1M; the solid-liquid ratio of the second product to the coating solution is 1g:(100mL~300mL). The inventors obtained the above-mentioned concentration range of the transition metal source through extensive experiments and precise calculations to more effectively promote the uniform growth of transition metal sulfides or selenides on the surface of the cathode material, while reducing the formation of byproducts caused by excess transition metal source, thereby enabling more efficient bonding with sulfur / selenium atoms to form a second coating layer with more uniform thickness and better crystallinity. The preferred solid-liquid ratio range also allows the second product particles to be more fully immersed in the coating solution, thus promoting more uniform growth of transition metal sulfides / selenides and reducing the problem of uneven coating layer growth caused by an improper solid-liquid ratio, or the problem of excessively thick coating layers increasing charge transport resistance. Ultimately, the controllable growth of the second coating layer was achieved more effectively at the microstructural level, forming a more stable heterojunction interface layer, which significantly improved the electrochemical performance of the obtained coated cathode material.

[0038] In the hydrothermal reaction process, the preferred reaction temperature is 200±20℃ and the time is 12±2h. This more effectively promotes the chemical reaction between transition metal ions and sulfur / selenium atoms from the perspective of reaction thermodynamics, forming a transition metal sulfide / selenide layer with higher crystallinity and more controllable thickness, and ultimately further improves the electrochemical activity and cycle stability of the final coated cathode material.

[0039] In practical applications, to form a more electronically stable heterojunction interface layer with the first coating layer, thereby further optimizing the performance of the resulting coated cathode material, the preferred transition metal source is selected from one or more of molybdenum, tungsten, vanadium, and niobium sources; the sulfur source is selected from one or more of thiourea, thioacetamide, and sodium sulfide; and the selenium source is selected from one or more of selenourea, selenium dioxide, and sodium selenite. More specifically, among the aforementioned transition metal sources: the molybdenum source is selected from one or more of ammonium molybdate, sodium molybdate, and calcium molybdate; the tungsten source is selected from one or more of ammonium tungstate, tungsten hexachloride, and sodium tungstate; the vanadium source is selected from one or more of ammonium metavanadate, vanadium pentoxide, and vanadium trichloride; and the niobium source is selected from one or more of niobium pentachloride, niobium oxalate, and ammonium niobate.

[0040] In step S4, the preferred heat treatment temperature is 300℃~500℃, and the time is 1h~3h, to further improve crystallinity and promote structural integration between transition metal sulfides / selenides and two-dimensional non-metallic materials, enhancing the stability of the heterojunction interface and thus significantly optimizing the electrochemical activity of the resulting coated cathode material. Furthermore, to reduce the introduction of impurities and further improve the conductivity of the resulting coated cathode material, the heat treatment is preferably carried out in a protective atmosphere or a reducing atmosphere, wherein the protective atmosphere is nitrogen and / or argon, and the reducing atmosphere is a mixture of hydrogen and argon, wherein the hydrogen gas fraction is 5%~10%.

[0041] A third aspect of the present invention provides a positive electrode sheet comprising the aforementioned coated positive electrode material; or, the positive electrode sheet comprising a coated positive electrode material prepared by the aforementioned method for preparing the coated positive electrode material. By employing the aforementioned carefully designed coated positive electrode material, the corresponding positive electrode sheet exhibits significant improvements in energy density, cycle stability, and rate performance. In battery applications, the resulting positive electrode sheet can withstand higher current densities, exhibits lower internal resistance and higher energy output capability, which is beneficial for improving the overall performance of the battery.

[0042] A fourth aspect of the present invention provides a lithium-ion battery comprising the aforementioned positive electrode sheet. By applying the positive electrode sheet of the present invention to a lithium-ion battery, the resulting battery exhibits higher energy density, longer cycle life, and superior rate performance. In particular, the microstructure improvement of the coated positive electrode material in the electrode sheet effectively solves the problems of voltage decay and capacity degradation of the positive electrode material during charge and discharge, improving the battery's voltage retention rate and capacity retention rate. Furthermore, the heterojunction coating layer on the surface of the coated positive electrode material provided by the present invention enhances the interfacial stability with the electrolyte, reduces the dissolution of transition metals, and reduces the formation of the SEI film, thereby significantly reducing the battery's internal resistance and improving high-voltage stability.

[0043] The present application will be further described in detail below with reference to specific embodiments, which should not be construed as limiting the scope of protection claimed in the present application.

[0044] Unless otherwise defined, all technical terms used herein have the same meaning as commonly understood by those skilled in the art. The technical terms used herein are for the purpose of describing particular embodiments only and are not intended to limit the scope of the invention.

[0045] Example 1

[0046] A method for preparing a coated cathode material:

[0047] (1) Cathode material pretreatment: LiMn 0.5 Fe 0.5 PO4 particles (average particle size 3 μm) were dispersed in an ethanol / water mixed solution (ethanol:water = 3:1, volume ratio) at a solid-liquid ratio of 1 g: 100 mL and ultrasonicated at 40 kHz for 30 minutes to hydroxylate the particle surface, thus obtaining the first product.

[0048] (2) Graphene layer deposition: Graphene oxide (GO) dispersion (concentration of 1 mg / mL) was mixed with pretreated cathode particles at a solid-liquid ratio of 1 g: 150 mL and stirred at 500 rpm for 2 hours. GO was uniformly coated on the particle surface by electrostatic adsorption, thus forming the second product. Then, an appropriate amount of ascorbic acid was added (the weight ratio of the second product to the added ascorbic acid was 10:1), and the GO was reduced at 80 °C for 2 hours to convert GO into reduced graphene oxide (rGO).

[0049] (3) In-situ growth of MoS2 layer: Prepare an aqueous solution containing 0.05M (NH4)2MoS4 and 0.1M thiourea; add the positive electrode particles coated with rGO to the above solution at a solid-liquid ratio of 1g:300mL, then transfer to a reactor and hydrothermally react at 200℃ for 12 hours; MoS2 nanosheets grow in situ on the surface of rGO to form a second coating layer, and thus obtain the third product. During this process, due to the difference in work function between the rGO layer and the MoS2 layer, electrons will transfer from the rGO layer to the MoS2 layer in order to achieve Fermi level equilibrium, thereby forming a built-in electric field at the interface, i.e., the heterojunction interface layer.

[0050] (4) Heat treatment: The third product is heat-treated at 400°C for 2 hours in an argon atmosphere to enhance the bonding force between the outer coating layer and the cathode particles, thus obtaining the coated cathode material.

[0051] The TEM characterization results of the obtained coated cathode material are shown in the figure. Figure 1In the structure of the obtained material, the thickness of the rGO layer is 2 nm and the thickness of the MoS2 layer is 4 nm (i.e., the total thickness of the two is 6 nm, and the thickness ratio is 1:2).

[0052] Example 2

[0053] A method for preparing a coated cathode material:

[0054] The only difference between this embodiment and Embodiment 1 is that in step (1), LiMn is... 0.5 Fe 0.5 The solid-liquid ratio of PO4 particles to the ethanol / water mixture was changed to 1g:40mL.

[0055] In the structure of the obtained coated cathode material, the thickness of the rGO layer is 1 nm and the thickness of the MoS2 layer is 3 nm (that is, the total thickness of the two is 4 nm, and the thickness ratio is 1:3).

[0056] Example 3

[0057] A method for preparing a coated cathode material:

[0058] The only difference between this embodiment and Embodiment 1 is that in step (1), LiMn is... 0.5 Fe 0.5 The solid-liquid ratio of PO4 particles to the ethanol / water mixture was changed to 1g:200mL.

[0059] In the structure of the obtained coated cathode material, the thickness of the rGO layer is 3 nm and the thickness of the MoS2 layer is 6 nm (i.e., the total thickness of the two is 9 nm, and the thickness ratio is 1:2).

[0060] Example 4

[0061] A method for preparing a coated cathode material:

[0062] The only difference between this embodiment and embodiment 1 is that in step (2), the solid-liquid ratio of the GO dispersion to the pretreated positive electrode particles is changed to 1g:60mL.

[0063] In the structure of the obtained coated cathode material, the thickness of the rGO layer is 4 nm and the thickness of the MoS2 layer is 4 nm (that is, the total thickness of the two is 8 nm, and the thickness ratio is 1:1).

[0064] Example 5

[0065] A method for preparing a coated cathode material:

[0066] The only difference between this embodiment and embodiment 1 is that in step (2), the solid-liquid ratio of the GO dispersion to the pretreated positive electrode particles is changed to 1g:240mL.

[0067] In the structure of the obtained coated cathode material, the thickness of the rGO layer is 1 nm and the thickness of the MoS2 layer is 4 nm (i.e., the total thickness of the two is 5 nm, and the thickness ratio is 1:4).

[0068] Example 6

[0069] A method for preparing a coated cathode material:

[0070] The only difference between this embodiment and embodiment 1 is that in step (3), the solid-liquid ratio of the positive electrode particles coated with rGO to the coating solution is changed to 1g:80mL.

[0071] In the structure of the obtained coated cathode material, the thickness of the rGO layer is 2nm and the thickness of the MoS2 layer is 2nm (i.e., the total thickness of the two is 4nm, and the thickness ratio is 1:1).

[0072] Example 7

[0073] A method for preparing a coated cathode material:

[0074] The only difference between this embodiment and embodiment 1 is that in step (3), the solid-liquid ratio of the positive electrode particles coated with rGO to the coating solution is changed to 1g:350mL.

[0075] In the structure of the obtained coated cathode material, the thickness of the rGO layer is 2 nm and the thickness of the MoS2 layer is 6 nm (i.e., the total thickness of the two is 8 nm, and the thickness ratio is 1:3).

[0076] Example 8

[0077] A method for preparing a coated cathode material:

[0078] The only difference between this embodiment and embodiment 1 is that in step (3), the reaction temperature of the hydrothermal reaction is changed to 150°C and the reaction time is changed to 15h.

[0079] In the structure of the obtained coated cathode material, the thickness of the rGO layer is 2 nm and the thickness of the MoS2 layer is 5 nm (that is, the total thickness of the two is 7 nm, and the thickness ratio is 1:2.5).

[0080] Example 9

[0081] A method for preparing a coated cathode material:

[0082] The only difference between this embodiment and embodiment 1 is that in step (3), the reaction temperature of the hydrothermal reaction is changed to 250°C and the reaction time is changed to 8h.

[0083] In the structure of the obtained coated cathode material, the thickness of the rGO layer is 2nm and the thickness of the MoS2 layer is 3nm (that is, the total thickness of the two is 5nm, and the thickness ratio is 1:1.5).

[0084] Example 10

[0085] A method for preparing a coated cathode material:

[0086] The only difference between this embodiment and embodiment 1 is that in step (4), the heat treatment holding temperature is changed to 200°C and the holding time is changed to 4h.

[0087] In the structure of the obtained coated cathode material, the thickness of the rGO layer is 4 nm and the thickness of the MoS2 layer is 6 nm (that is, the total thickness of the two is 10 nm, and the thickness ratio is 1:3).

[0088] Example 11

[0089] A method for preparing a coated cathode material:

[0090] The only difference between this embodiment and embodiment 1 is that in step (4), the heat treatment holding temperature is changed to 600°C and the holding time is changed to 0.5h.

[0091] In the structure of the obtained coated cathode material, the thickness of the rGO layer is 1 nm and the thickness of the MoS2 layer is 2 nm (that is, the total thickness of the two is 3 nm, and the thickness ratio is 1:2).

[0092] Comparative Example 1

[0093] A cathode material: directly using commercially available LiMn 0.5 Fe 0.5 PO4 particles (i.e., the core particles in Example 1) are used as the cathode material.

[0094] Comparative Example 2

[0095] A method for preparing a coated cathode material:

[0096] The only difference between this comparative example and Example 1 is that steps (3) and (4) were not performed; instead, the second product obtained after reduction in step (2) was directly used as the coated cathode material sample.

[0097] Comparative Example 3

[0098] A method for preparing a coated cathode material:

[0099] This comparative example is the same as step (1) of Example 1, but the subsequent steps are different.

[0100] (2) In-situ growth of MoS2 layers: An aqueous solution containing 0.05 M (NH4)2MoS4 and 0.1 M thiourea was prepared; the first product was added to the above solution, and then transferred to a reaction vessel for hydrothermal reaction at 200 °C for 12 hours; MoS2 nanosheets were grown on LiMn 0.5 Fe 0.5 The PO4 particles grow in situ to form the first coating layer, which in turn yields the second product.

[0101] (3) Graphene layer deposition: Graphene oxide (GO) dispersion (concentration 1 mg / mL) and the second product were mixed at a solid-liquid ratio of 1g:150mL and stirred at 500rpm for 2 hours. GO was uniformly coated on the particle surface by electrostatic adsorption, thereby forming the third product. Then, an appropriate amount of ascorbic acid was added (the weight ratio of the second product to the added ascorbic acid was 10:1), and the product was reduced at 80℃ for 2 hours to convert GO into reduced graphene oxide (rGO).

[0102] (4) Heat treatment: The third product is heat-treated at 400°C for 2 hours in an argon atmosphere to enhance the bonding force between the outer coating layer and the cathode particles, thus obtaining the coated cathode material.

[0103] Battery Sample Preparation and Testing Methods

[0104] The positive electrode materials obtained in the above embodiments and comparative examples were used to prepare electrodes according to the following method: Positive electrode material, conductive carbon black (Super P), and binder polyvinylidene fluoride (PVDF) were uniformly mixed at a mass ratio of 8:1:1, and N-methylpyrrolidone (NMP) was used as the dispersion solvent. The mixture was thoroughly stirred and dispersed to obtain a uniform positive electrode slurry. The obtained positive electrode slurry was uniformly coated onto the surface of an aluminum foil current collector, pre-dried at 80°C, rolled, and sliced ​​to obtain a circular positive electrode sheet. The positive electrode sheet was then thoroughly dried under vacuum at 120°C to remove residual solvent and moisture. The prepared positive electrode sheet was matched with a lithium metal negative electrode to assemble a CR2032 type coin cell. A polypropylene porous membrane was used as the battery separator, and a mixed solution of ethylene carbonate / dimethyl carbonate (EC:DMC volume ratio of 1:1) containing 1 mol / L lithium hexafluorophosphate (LiPF6) was used as the electrolyte. Coin cell samples with a rated capacity of 2.0~3.0 mAh were assembled.

[0105] Each battery sample was subjected to charge-discharge tests within a voltage range of 2.0V to 4.5V to obtain the first discharge capacity and first efficiency at a 0.2C rate. Then, charge-discharge cycles were performed at a 1C rate to obtain the discharge capacity (which is the first discharge capacity after the current density is switched from 0.2C to 1C) and the capacity retention rate after 100 cycles.

[0106] The performance test results are shown in Table 1.

[0107] Table 1

[0108]

[0109] As can be seen from the above description, the embodiments of the present invention construct a synergistic coating structure consisting of a two-dimensional non-metallic layer and a transition metal compound layer on the surface of the positive electrode active material, thereby forming a heterojunction interface layer and obtaining a high-performance coated positive electrode material. The resulting coated positive electrode material possesses superior electrochemical activity and cycle stability, thus enabling the lithium-ion battery to achieve higher electrical performance and a longer service life.

[0110] Specifically, in each embodiment:

[0111] Comparing Examples 2 and 3 with Example 1, it can be seen that in step S1, by optimizing the solid-liquid ratio of the positive electrode material particles to the hydroxylation solvent, the hydroxylation of the positive electrode particles can be fully promoted, while reducing their accumulation phenomenon, further improving the hydroxylation efficiency and the uniformity of hydroxylation, and providing a better foundation for subsequent electrostatic adsorption coating.

[0112] Comparing Examples 4 and 5 with Example 1, it can be seen that in step S2, by optimizing the solid-liquid ratio of the first product to the dispersion, a dense first coating layer can be formed, and the phenomenon of incomplete adsorption caused by too little solution or excessive coating layer caused by too much solution can be reduced more effectively. Thus, the electrochemical performance of the obtained coated cathode material is significantly optimized in terms of microstructure.

[0113] Comparing Examples 6 and 7 with Example 1, it can be seen that in step S3, by optimizing the solid-liquid ratio of the second product to the coating solution, the second product particles can be more fully immersed in the coating solution. This facilitates more uniform growth of the transition metal sulfide / selenide, reducing the problems of uneven coating layer growth caused by improper solid-liquid ratio or excessively thick coating layer increasing charge transport resistance. Ultimately, controllable growth of the second coating layer is achieved more effectively at the microstructural level, forming a more stable heterojunction interface layer, and significantly improving the electrochemical performance of the obtained coated cathode material.

[0114] Comparing Examples 8 and 9 with Example 1, it can be seen that in step S3, by optimizing the reaction conditions of the hydrothermal reaction, the chemical reaction between transition metal ions and sulfur / selenium atoms can be promoted more effectively from the perspective of reaction thermodynamics, forming a transition metal sulfide / selenide layer with higher crystallinity and more controllable thickness, and ultimately further improving the electrochemical activity and cycle stability of the final coated cathode material.

[0115] Comparing Examples 10 and 11 with Example 1, it can be seen that in step S4, by optimizing the heat treatment conditions, the crystallinity can be further improved, while promoting the structural integration between transition metal sulfides / selenides and two-dimensional non-metallic materials, enhancing the stability of the heterojunction interface, and thus more significantly optimizing the electrochemical activity of the obtained coated cathode material.

[0116] It should be noted that the terms "first," "second," etc., used in the specification and claims of this application are used to distinguish similar objects and are not necessarily used to describe a specific order or sequence. It should be understood that such terms can be used interchangeably where appropriate so that the embodiments of this application described herein can be implemented, for example, in a sequence other than those described herein.

[0117] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A coated cathode material, comprising core particles and an outer coating layer, characterized in that, The core particles are selected from one or more of phosphate materials, nickel-cobalt-manganese ternary materials, and lithium-rich manganese-based materials; Along a direction away from the core particle, the outer coating layer includes a first coating layer and a second coating layer; The first coating layer includes a two-dimensional non-metallic material, the second coating layer includes a transition metal sulfide and / or a transition metal selenide, and a heterojunction interface layer is formed between the first coating layer and the second coating layer through van der Waals forces.

2. The coated cathode material according to claim 1, characterized in that... ; The particle size of the core particles is 2μm~5μm; The thickness of the outer coating layer is 2nm~20nm, and the thickness ratio of the first coating layer to the second coating layer is 1:(1~3). Preferably, the thickness of the first coating layer is 1 nm to 5 nm; and / or, the thickness of the second coating layer is 1 nm to 15 nm.

3. The coated cathode material according to claim 1 or 2, characterized in that, The first coating layer includes one or more of graphene, reduced graphene, and boron nitride nanosheets; and / or, In the second coating layer, the transition metal sulfide is selected from one or more of MoS2, WS2, VS2 and NbS2, and the transition metal selenide is MoSe2 and / or WSe2.

4. A method for preparing a coated cathode material, characterized in that, include: Step S1: Perform surface hydroxylation treatment on the cathode material particles to obtain the first product; Step S2: The first product undergoes an electrostatic adsorption reaction with a two-dimensional non-metallic material to form a first coating layer on the surface of the first product, thereby obtaining the second product. Step S3: The second product undergoes a hydrothermal reaction with the coating solution to obtain the third product; The coating solution includes a transition metal source, and the coating solution also includes a sulfur source and / or a selenium source; during the hydrothermal reaction, the transition metal source reacts in situ with the sulfur source and / or the selenium source and coats the surface of the second product to form a second coating layer, thereby obtaining the third product; In step S4, the third product is heat-treated to obtain the coated cathode material.

5. The method for preparing the coated cathode material according to claim 4, characterized in that, Step S1 includes: dispersing the positive electrode material particles in a hydroxylation solvent containing alcohols, and performing the surface hydroxylation treatment by ultrasound to obtain the first product; The solid-liquid ratio of the positive electrode material particles to the hydroxylation solvent is 1 g: (50 mL ~ 150 mL). The frequency of the ultrasonic treatment is 30kHz~60kHz, and the time is 20min~40min; The alcohols are selected from one or more of ethanol, ethylene glycol, and isopropanol.

6. The method for preparing the coated cathode material according to claim 4 or 5, characterized in that, Step S2 includes: preparing a dispersion of the two-dimensional non-metallic material, adding the first product to the dispersion, and carrying out the electrostatic adsorption reaction by stirring, so that the two-dimensional non-metallic material forms the first coating layer on the surface of the first product, thereby obtaining the second product; In the dispersion, the concentration of the two-dimensional non-metallic material is 1 ± 0.05 mg / mL; The solid-liquid ratio of the first product to the dispersion is 1 g: (80 mL ~ 200 mL). The two-dimensional non-metallic material is graphene and / or boron nitride nanosheets; The stirring speed is 300 rpm to 800 rpm, and the stirring time is 1.5 h to 2.5 h; Preferably, the two-dimensional non-metallic material is graphene, and step S2 further includes: using ascorbic acid to reduce the second product so that the graphene in the first coating layer is reduced to reduced graphene; More preferably, the reduction treatment is carried out at a reaction temperature of 80±5℃ for a time of 1.5h~2.5h; More preferably, the weight ratio of the second product to the ascorbic acid is (10~20):

1.

7. The method for preparing the coated cathode material according to any one of claims 4 to 6, characterized in that, In step S3 In the coating solution, the concentration of the transition metal source is 0.04M~0.06M, and the concentrations of the sulfur source and the selenium source are each independently 0~0.1M; The solid-liquid ratio of the second product to the coating solution is 1 g: (100 mL ~ 300 mL). The hydrothermal reaction was carried out at a temperature of 200±20℃ for 12±2h. Preferably, the transition metal source is selected from one or more of molybdenum, tungsten, vanadium, and niobium; the sulfur source is selected from one or more of thiourea, thioacetamide, and sodium sulfide; and the selenium source is selected from one or more of selenourea, selenium dioxide, and sodium selenite. More preferably, the molybdenum source is selected from one or more of ammonium molybdate, sodium molybdate, and calcium molybdate; the tungsten source is selected from one or more of ammonium tungstate, tungsten hexachloride, and sodium tungstate; the vanadium source is selected from one or more of ammonium metavanadate, vanadium pentoxide, and vanadium trichloride; and the niobium source is selected from one or more of niobium pentachloride, niobium oxalate, and ammonium niobate.

8. The method for preparing the coated cathode material according to any one of claims 4 to 7, characterized in that, In step S4 The heat treatment temperature is 300℃~500℃, and the time is 1h~3h; The heat treatment is carried out in a protective atmosphere or a reducing atmosphere, wherein the protective atmosphere is nitrogen and / or argon, and the reducing atmosphere is a mixture of hydrogen and argon, wherein the hydrogen gas fraction is 5% to 10%.

9. A positive electrode sheet, characterized in that, The positive electrode sheet includes the coated positive electrode material according to any one of claims 1 to 3; or, the positive electrode sheet includes the coated positive electrode material prepared by the preparation method of the coated positive electrode material according to any one of claims 4 to 8.

10. A lithium-ion battery, characterized in that, The lithium-ion battery includes the positive electrode sheet as described in claim 9.